Acoustic Monitoring of Oxygen Ebullition Reveals Hidden Productivity in a Seemingly Heterotrophic Seagrass Meadow - Kyle A. Capistrant-Fossa; Megan S. Ballard; Kevin M. Lee; Colby W. Cushing; Andrew R. McNeese; Thomas S. Jerome; Preston S. Wilson; Kenneth H. Dunton (Ocean-Land-Atmosphere Research)
Oxygen ebullition is typically ignored in long-term measurements of net ecosystem productivity (NEP), which reflects whether systems are net heterotrophic or autotrophic based on diel changes in oxygen. The solubility of oxygen in seawater is a function of temperature, salinity, and pressure. Warm, high-salinity seawater has low oxygen solubility, and when combined with the photosynthetic productivity of macrophytes in shallow, clear waters, oxygen ebullition frequently occurs. The presence of mixed-phase oxygen in supersaturated seawater creates difficulties for oxygen measurements because sensors cannot measure dissolved and gas phases simultaneously. Therefore, dissolved oxygen measurements must be taken in conjunction with separate ebullition measurements to develop an accurate oxygen budget needed to characterize NEP. Here, we seek to understand the drivers of NEP for a Thalassia testudinum meadow in the Gulf of Mexico and calculate ebullition rates using acoustic sensing. We hypothesize that oxygen ebullition will substantially increase NEP, particularly during the summer months because of photosynthetic dependence on temperature and irradiance. We found that the seagrass meadow is typically oxygen saturated during the hours 0700 to 2200 with maximum saturation occurring at 1400. Acoustic-based methods and general additive modeling both found highest ebullition rates in July/August. High respiration led to an apparent net heterotrophic system (NEP = −2.1 mmol O2 m−2 d−1), but accounting for air–sea exchange and ebullition causes the system to be autotrophic (NEP = 54 mmol O2 m−2 d−1). This study demonstrates the importance of including ebullition into NEP calculations and the viability of acoustics as a tool for monitoring aquatic productivity.